Long-term management of patients with autoimmune encephalitis: a systematic review - Daniela Inês Figueiredo Pires (2022)
Introduction: We sought to critically summarize the existing literature on patients with Autoimmune Encephalitis, aiming to clarify if there is enough scientific evidence to support the recommendation of a specific strategy of follow-up and long-term management of these patients. Results: 37 studies were included in this review, with 1515 patients reviewed, out of which only 68,4% had any mention of follow-up. 6,8% patients had a registry of relapse, a tumor was detected in 13,3% and 5,3% passed away. Conclusion: This review shows there is a large gap of knowledge on the long-term management of patients with Autoimmune Encephalitis.